Teaching Speaking by Applying Flipped Learning Model in ELT Class: A Best Practice - Elsa Desi Putri; Achmad Yani (Universitas Negeri Malang, 2023)
The advancement of communication and information technologies had provided a flexible learningenvironment. In addition, the 21st century teachers were expected to be able to integrate technologyinto their teaching and learning process. One of the learning models that could facilitate thisintegration was the flipped learning model. However, it was considered as a new learning model inIndonesian context, where there were not many teachers applied this learning model into theirteaching and learning process. Additionally, there was few research conducted on the implementationthis learning model in teaching speaking. For this purpose, this paper aimed to provide a best practiceof the implementation of the flipped learning in the teaching of speaking. The implementation of theflipped learning was applied to the EFL learners who are in the beginner level. One of the materialstaken to be taught with the purpose of improving the learners’ speaking to specifically talk by usingpresent perfect tense. Finally, this paper illustrated how those implementations are applied to theteaching and learning process.